UTERINE FIBROIDS GOING INTO THE HEART: INTRAVASCULAR AND INTRA-CARDIAC LEIOMYOMATOSIS: A VERY UNUSUAL PRESENTATION - Siddique Umer, Ummara; Ghaus, Syed; Alam, Shahjehan; Gul, Seema (Journal of Postgraduate Medical Institute, 2016)
This case report is of a 50 years old female who presented with vague history of long term abdominal pain, shortness of breath and echocardiographic suspicion of right atrial mass. She was investigated using 128-slice Multidetector Computed tomography (MDCT) scanner in the Department of Radiology. Images of lower chest, entire abdomen and pelvis were taken in venous phase. On CT images of our patient, uterus was significantly enlarged and replaced by multiple contour deforming fibroids, which were involving the right adnexa, invading the right ovarian vessels, and extending into the right ovarian vein, inferior vena cava (IVC) and right atrium of heart. The findings were confirmed on surgery. Surgery also confirmed extension into right ventricle and pulmonary arteries i.e. pulmonary leiomyomatosis emboli. The histological findings were consistent with intravascular leiomyoma. MDCT images play instrumental role for preoperative morphologic assessment of IVL as it can easily identify the precise location, extent and provide a roadmap for the surgeons.